Hypotonicity‐Induced WNK1 Phosphorylation Prevents H 2 O 2 ‐Induced Apoptosis in Vascular Smooth Muscle Cells - Yajuan Zhang; Wei Lin; Fengting Lu; Zhujun Liang; Chengcui Huang; Ma mingming; Liang Sijia; Pang Ruiping; Jiaguo Zhou; Yongyuan Guan; Guozheng Liang; Xiaofei Lv (Basic & Clinical Pharmacology & Toxicology, 2026)
ABSTRACT Vascular smooth muscle cells (VSMCs) are essential for maintaining arterial wall integrity, with their associated apoptosis critically involved in cardiovascular diseases. Intracellular chloride anion (Cl − ) dysregulation is closely linked to apoptosis. However, the underlying mechanism via chloride‐sensitive kinases remains unclear. Here, we show that hypotonic stimulation activates volume‐regulated chloride channels (VRCCs) and induces the phosphorylation of the chloride‐sensitive kinase WNK1. Activated WNK1 protects VSMCs against H 2 O 2 ‐induced apoptosis by maintaining the Bcl‐2/Bax balance, preserving mitochondrial membrane potential and inhibiting caspase‐9/3 activation. These findings uncover a novel protective role of WNK1 in VRCC‐mediated Cl − signalling and provide new perspectives for targeting chloride‐sensitive kinases in the treatment of hypertension and related cardiovascular diseases.